2005
DOI: 10.1111/j.1365-2966.2004.08379.x
|View full text |Cite
|
Sign up to set email alerts
|

The 2dF QSO Redshift Survey - XIV. Structure and evolution from the two-point correlation function

Abstract: In this paper we present a clustering analysis of quasi‐stellar objects (QSOs) using over 20 000 objects from the final catalogue of the 2dF QSO Redshift Survey (2QZ), measuring the redshift‐space two‐point correlation function, ξ(s). When averaged over the redshift range 0.3 < z < 2.2 we find that ξ(s) is flat on small scales, steepening on scales above ∼25 h−1 Mpc. In a WMAP/2dF cosmology (Ωm= 0.27, ΩΛ= 0.73) we find a best‐fitting power law with s0= 5.48+0.42−0.48 h−1 Mpc and γ= 1.20 ± 0.10 on scales s= 1 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

92
464
5
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 369 publications
(566 citation statements)
references
References 87 publications
(164 reference statements)
92
464
5
4
Order By: Relevance
“…Similar results for b 0 were obtained by Basilakos et al (2005), who also studied the bias evolution for both clustering models. Gilli et al (2009) found b 0 values in the range 1.5-2, similar to that of Croom et al (2005), consistent with our predictions for a = −3 clustering scenario.…”
Section: Bias Parameter and Connection To Dark Matter Haloessupporting
confidence: 81%
See 2 more Smart Citations
“…Similar results for b 0 were obtained by Basilakos et al (2005), who also studied the bias evolution for both clustering models. Gilli et al (2009) found b 0 values in the range 1.5-2, similar to that of Croom et al (2005), consistent with our predictions for a = −3 clustering scenario.…”
Section: Bias Parameter and Connection To Dark Matter Haloessupporting
confidence: 81%
“…In general, X-ray selected AGN show larger bias parameters than optically selected AGN (e.g. Croom et al 2005;Myers et al 2007). This could mean that the underlying matter distribution is traced differently in Xrays and in the optical domain, with X-ray selected AGN residing in more massive DMH than the optically selected AGN.…”
Section: Bias Parameter and Connection To Dark Matter Haloesmentioning
confidence: 99%
See 1 more Smart Citation
“…Brodwin et al (2008) found that DOGs selected above a 24 µm flux density S 24 > 0.3 mJy have r 0 = 7.4h −1 Mpc, quite similar to the Hickox et al (2012) autocorrelation length of SMGs of r 0 = 7.7h −1 Mpc. The inferred halo masses for luminous SMGs and DOGs are not terribly dissimilar from constraints on optically-selected quasars (Croom et al, 2005;White et al, 2012).…”
Section: Clustering Of Dsfgsmentioning
confidence: 69%
“…The total survey area is 721.6 deg 2 , when allowance is made for regions of sky excised around the bright stars. The QSO candidates for the 2QZ (18.25 < b J < 20.85) were selected based on fulfilling at least one of the following colour criteria: [7,18,19] and for the 6QZ (16.0 < b J < 18.25) the colour criteria is u − b J ≤ −0.50 [18,23]. The data from both the 2dF and 6dF were reduced using the pipeline data reduction system 2DFDR [24].…”
Section: The Datamentioning
confidence: 99%